Heurtistics Evaluation Techniques In Agile Software Model For The Development Of Usable Software - Butt, Saad Masood; Azura, Onn; Mazlina, Abdul Majid (Publications International, 2014)
Majority of agile projects currently involve interactive user interface designs, which can only be possible by following UCD in agile software model. But the integration of UCD is not clear in the current agile models. Both Agile models and UCD have iterative nature but agile models focus on coding and development of software; whereas, UCD focuses on user interface of the software. Similarly, both of them have testing features where the agile model involves automated tested code while UCD involves an expert or a user to test the user interface. In this paper, a new agile usability model is presented and tested in companies and are presented. Key results from these projects clearly shows: the proposed agile model incorporates usability evaluation methods, improve the relationship between usability experts to work with agile software experts; in addition, allows agile developers to incorporate the result from UCD into subsequent interactions.